MODEL NHT (NUMBER HEAD TOGETHER ) SALAH SATU ALTERNATIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI MATRIKS DI KELAS XI MIA B SMAN 1 LAWANG KIDUL - Novti Dewita (Dwija Inspira: Jurnal Pendidikan Multi Perspektif, 2018)
The purpose of this paper is to improve student learning outcomes of class XI MIA B in SMA Negeri 1 Lawang Kidul on Matrix material by using NHT learning model. Based on the daily test analysis that has been implemented on the previous basic competence stated that the results of classical learning 50% below KKM. This discussion was held in two stages with the subject of observation is the students of class XI MIA B Lawang Kidul SMAN 1 Lawang Kidul Muara Enim district of South Sumatra Province. Data collection is done through the item of test and observation sheet of student activity. From the data analysis, the students’ learning result data increased by 20.6%. It can be concluded that the implementation of the NHT Learning Model can improve student learning outcomes in matrix aterial in class XI MIA B in SMAN 1 Lawang Kidul.